Investigating an Ethical Approach to Genetically Modified Crops in Environmental Educational Processes - Stephan le Roux; Johanna G Ferreira (Environmental Association of Southern Africa, 2006)
enetically modified (GM) crops gained attention in southern Africa in the context of broader debates about the struggle for food security and poverty alleviation to achieve sustainable development. The prospects of GM crops as a technological innovation have provoked numerous debates and environmental concern groups have challenged their use. Environmental educators' concern for greater ethical practices regarding environmental issues can be applied to the subject of GM crops. This article focuses on the perceptions of environmental educators regarding the use of GM crops towards sustainable development. Interviews were conducted with a small group of environmental educators to gain some insight into their perceptions. The interviews reflected some contextual relevance of GM crops, understanding of the concepts 'GM crops' and 'sustainable development' as well as four unique themes. These emphasise the plurality of the GM crops issue and the importance thereof in working towards an ethical approach in environmental educational processes.